How fins affect the economy and efficiency of human swimming - Zamparo, P.; Pendergast, D. R.; Termin, B.; Minetti, A. E. (The Journal of Experimental Biology, 2002)
The aim of the present study was to quantify the improvements in the economy and efficiency of surface swimming brought about by the use of fins over a range of speeds (v) that could be sustained aerobically. At comparable speeds, the energy cost (C) when swimming with fins was about 40 % lower than when swimming without them; when compared at the same metabolic power, the decrease in C allowed an increase in v of about 0.2 ms-1. Fins only slightly decrease the amplitude of the kick (by about 10 %) but cause a large reduction (about 40 %) in the kick frequency. The decrease in kick frequency leads to a parallel decrease of the internal work rate (int, about 75 % at comparable speeds) and of the power wasted to impart kinetic energy to the water (k, about 40 %). These two components of total power expenditure were calculated from video analysis (int) and from measurements of Froude efficiency (k). Froude efficiency (F) was calculated by computing the speed of the bending waves moving along the body in a caudal direction (as proposed for the undulating movements of slender fish); F was found to be 0.70 when swimming with fins and 0.61 when swimming without them. No difference in the power to overcome frictional forces (d) was observed between the two conditions at comparable speeds. Mechanical efficiency [tot/(Cv), where tot=k+int+d] was found to be about 10 % larger when swimming with fins, i.e. 0.13±0.02 with and 0.11±0.02 without fins (average for all subjects at comparable speeds).